Street Talk - Avital Ronell (Studies in 20th & 21st Century Literature, 1986)
This essay investigates the fragile intersection where rumor and a more "authentic" modality of language can be shown to cross over into one another. Treating the relationship of Benjamin, Heidegger and Rousseau to rumoro-logical paranoia, "Street-Talk" interprets the epistemological teetering between the knowing and not-knowing around which Fama articulates her power. All three of these thinkers are shown to be exemplarily afflicted by rumorous utterances and share a drive to create, in their works, a rumor control center. Often these controls take over the features which they attempt to disown; thus the greatest moment of truth-telling appropriates the form of inferential small-talk. The essay analyzes a temporality of writing disclosed by Rousseau's Promenades in terms of an après-ma-mort structure. Finally, guided by Blanchot's insights and Huet's notion of monsterized publicity, the essay addresses the rapport of rumor to oeuvre: Ecce Fama.
Keywords: rumor; authentic; language; modality; Benjamin; Heidegger; Rousseau; rumoro-logical paranoia; knowing; not-knowing; Fama; truth-telling; small-talk; Promenades; après-ma-mort; structure; Blanchot; Huet; monsterized publicity; Ecce Fama